Pathologic features and clinical outcome of central neurocytoma: analysis of 15 cases - Li, Yu; Ye, Xiu-Feng; Qian, Guo; Yin, Yu; Pan, Qian-Guan (Chinese Journal of Cancer Research; Vol 24, No 4 (December 07, 2012): Chinese Journal of Cancer Research, 2012)
Objective: In order to get better recognition of central neurocytoma and diminish misdiagnose. Methods: A retrospective review identified 15 cases of central neurocytoma. All cases of central neurocytoma were analyzed for their clinical symptoms, pathologic changes, immunohistochemical staining, prognosis and differential diagnosis. Clinical follow-up was available for 11 patients. Results: There were 8 males and 7 females whose ages ranged from 10 to 64 years (median 32.93 years). The most common presenting symptoms were those related to increased intracranial pressure (ICP), including headache (100%), papilledema (93%) and vomiting (80%). All tumors were located in the ventricular system. The tumors were composed of uniform cells with round nuclei and a fine chromatin pattern and in some areas small cells with perinuclear halo could be seen. In particular, the anuclear areas may have a fine fibrillary matrix (neuropil). Nuclear atypia and vascular proliferation appeared in two cases, respectively. Focal necrosis could be seen in one case. Immunohistochemical findings included expression of synaptophysin [15/15], neuron specific enolase [12/15] and glial fibrillary acidic protein [3/15]. While MIB-1 proliferation index ranged from 0.8-12.5%, and were more than 2% in 3 of 15 cases assessed. Follow-up information was available for eleven patients. Conclusions: Central neurocytomas have a favorable prognosis in general, but in some cases the clinical course could be aggressive. Increase of GFAP positivity, proliferation index and vascular proliferation might suggest a more malignant process.